Transformation and bioavailability of metal oxide nanoparticles in aquatic and terrestrial environments. A review. (November 2017) - Amde, Meseret; Liu, Jing-fu; Tan, Zhi-Qiang; Bekana, Deribachew
Abstract: Metal oxide nanoparticles (MeO-NPs) are among the most consumed NPs and also have wide applications in various areas which increased their release into the environmental system. Aquatic (water and sediments) and terrestrial compartments are predicted to be the destination of the released MeO-NPs. In these compartments, the particles are subjected to various dynamic processes such as physical, chemical and biological processes, and undergo transformations which drive them away from their pristine state. These transformation pathways can have strong implications for the fate, transport, persistence, bioavailability and toxic-effects of the NPs. In this critical review, we provide the state-of-the-knowledge on the transformation processes and bioavailability of MeO-NPs in the environment, which is the topic of interest to researchers. We also recommend future research directions in the area which will support future risk assessments by enhancing our knowledge of the transformation and bioavailability of MeO-NPs. Graphical abstract: Highlights: Current state-of-the-knowledge on the transformation and bioavailability of MeO-NPs in the environment has been provided. Effects of MeO-NPs behavior on their transformations have been reviewed. Role of the transformation processes on bioavailability of the NPs have been discussed. Future research directions required to fill the existing research gaps have been provided. Abstract : Transformations of MeO-NPs depend on nature of the NPs themselves and chemistry of the medium, and can significantly affect their fate, bioavailability and toxic-effects.